Challenges In Teaching MAPEH: Perspectives of Grade 5 Teachers at Jones District, Isabela - Garcia, Mae Angelique (International Journal of Sustainability and Advanced Integrated Research, 2026)
MAPEH education plays a significant role in shaping well-rounded learners by blending Music, Arts, Physical Education, and Health into the school curriculum. This study took a closer look at the hurdles that Grade 5 teachers face when teaching MAPEH in Jones District, Isabela. It focused on teachers' backgrounds, the challenges they encountered, the teaching methods they used, and the activities they often incorporated into their lessons. Using a descriptive research design, this study relied on survey questionnaires to gather data. Twenty Grade 5 MAPEH teachers from selected public elementary schools were chosen as participants through purposive sampling. The data were analyzed using various statistical tools, such as frequency count, percentage, weighted mean, standard deviation, ANOVA, and regression analysis. The results showed that most teachers were experienced females who actively engaged in professional development. They faced challenges such as a shortage of teaching resources, limited student engagement, lack of equipment, and time constraints in their teaching. Despite these issues, teachers often use learner-centered methods such as cooperative learning, differentiated instruction, and inquiry-based learning. They also frequently employ interactive and movement-based activities to boost student participation and engagement. The statistical analysis highlighted significant links between the challenges faced and the teaching methods and activities used by the teachers in the study. The study concluded that while teachers showed skill and flexibility in MAPEH instruction, sufficient instructional support and resources are crucial for improving teaching effectiveness and student outcomes.
Keywords: MAPEH Instruction; Teaching Challenges; Grade 5 Teachers; Learner-Centered Teaching; Teaching Activities